Development of innovative flow visualisation methods to investigate the stages of Wet Compression Moulding (WCM) process. Issue 5 (August 2020) - Muthuvel, Balaji; Bhattacharyya, Debes; Bickerton, Simon
Abstract: The WCM is a novel production technique for fibre-reinforced polymer components. This technique is increasingly adopted in industry, typically in the automotive sector for medium to large-scale production. This process reduces the cost per part significantly by reducing the number of tools and processing steps, relative to Resin Transfer Moulding. To date, the processing variables, their relations and effect on the composite quality have been established through the knowledge gained by technologists. The drive of this research is to develop a fundamental understanding of the impact of process parameters (key process timings and cavity thicknesses, mould closing speed, edge clamping frame dimensions) and material properties (fibre reinforcement compaction response, permeability, and wettability together with test fluid viscosity and surface tension) on textile wetting, impregnation, and resulting composite part quality. In this study, a 480g/m 2 non-crimp unidirectional glass fibre reinforcement has been chosen and characterised for compaction response, in-plane, and through-thickness permeability. For ease of handling, motor oil (DTE heavy VG100) has been characterised and used as a test fluid. Two experimental flow visualisation setups have been developed at the CACM to investigate the influence of process and material parameters on initial resin application and textile wetting, and the subsequent compression flow stage.